Microbiome Analytics of the Gut Microbiota in Patients With Juvenile Idiopathic Arthritis: A Longitudinal Observational Cohort Study. Issue 6 (29th April 2019) - van Dijkhuizen, E. H. Pieter; Del Chierico, Federica; Malattia, Clara; Russo, Alessandra; Pires Marafon, Denise; ter Haar, Nienke M.; Magni‐Manzoni, Silvia; Vastert, Sebastiaan J.; Dallapiccola, Bruno; Prakken, Berent; Martini, Alberto; De Benedetti, Fabrizio; et al.
Abstract : Objective: To assess the composition of gut microbiota in Italian and Dutch patients with juvenile idiopathic arthritis (JIA) at baseline, with inactive disease, and with persistent activity compared to healthy controls. Methods: In a multicenter, prospective, observational cohort study, fecal samples were collected at baseline from 78 Italian and 21 Dutch treatment‐naive JIA patients with <6 months of disease duration and compared to 107 geographically matched samples from healthy children. Forty‐four follow‐up samples from patients with inactive disease and 25 follow‐up samples from patients with persistent activity were analyzed. Gut microbiota composition was determined by 16S ribosomal RNA–based metagenomics. Alpha‐ and β‐diversity were computed, and log ratios of relative abundance were compared between patients and healthy controls using random forest models and logistic regression. Results: Baseline samples from Italian patients showed reduced richness compared to healthy controls ( P < 0.001). Random forest models distinguished between Italian patient baseline samples and healthy controls and suggested differences between Dutch patient samples and healthy controls (areas under the curve >0.99 and 0.71, respectively). The operational taxonomic units (OTUs) of Erysipelotrichaceae (increased in patients), Allobaculum (decreased in patients), and Faecalibacterium prausnitzii (increased in patients) showed different relative abundance in Italian patient baseline samples compared to controls after controlling for multiple comparisons. Some OTUs differed between Dutch patient samples and healthy controls, but no evidence remained after controlling for multiple comparisons. No differences were found in paired analysis between Italian patient baseline and inactive disease samples. Conclusion: Our findings show evidence for dysbiosis in JIA patients. Only patient/control status, age, and geographic origin appear to be drivers of the microbiota profiles, regardless of disease activity stage, inflammation, and markers of autoimmunity.